Fertilizer use in pampean agroecosystems: impact on productivity and nutrient balance - Alvarez, Roberto (2015)
The Pampean Region of Argentina is one of the most suitable grain crop areas in the World with an annual production rounding 100 Mt. During the last four decades cropped surface with annual crops doubled, mostly because of the massive adoption of soybean [Glycine max (L.) Merr.] as main component of rotations, accounting at present for 60 % of the total seeded surface and resulting from the expansion over firstly livestock producing areas. The area cropped with other important species like wheat ( Triticum aestivum L.), corn (Zea mays L.), and sunflower (Helianthus annuus L.) remained nearly constant. In parallel to this, yields increased by two to three-fold leading to an overall increase of around four-fold of total grain production. Fertilizer use, that was null at the beginning of the seventies, rose exponentially, reaching 3.5 Mt yr–1 at present. Mainly, nitrogen and phosphorus fertilizers are applied at low rates. Soybean receives phosphorus fertilizers, meanwhile the others crops are fertilized both with nitrogen and phosphorus. Sulfur use is incipient in the Pampas and potassium is not applied because of the great amount naturally available in soils. Fertilization impact on productivity was assessed for by estimating crop responses to nutrient application in different pampean sub-regions taking into account soil fertility and crop response functions locally developed. Fertilizer technology accounts for 16% of the overall grain production of the region. Compared to other World agricultural regions this percentage is low and can be attributed to the high natural soil fertility, the low response of soybean to phosphorus application and its nitrogen fixation capacity. Nutrient balances in agro ecosystems were calculated as the differences between inputs, includingatmospheric nitrogen fixation, rainfall and fertilizer, and output using grain harvest and nutrient export information. The regional nitrogen balance for soil under agriculture is close to neutral at present, being the main input nitrogen fixed by soybean, which is equivalent to four times the input receive by fertilizer application. The balances of phosphorus, sulfur, and potassium are all negative. The impact of the negative phosphorus balance on soil fertility was assessed for by a regional survey which showed an average decrease of 70% in available phosphorus for crops up to 1 m depth. Future needs of fertilizer consumption for soil fertility maintenance were calculated and possible strategies for fertilizer technology use are discussed.